2018
DOI: 10.1111/pace.13411
|View full text |Cite
|
Sign up to set email alerts
|

Clinical parameters to optimize patient selection for subcutaneous and transvenous implantable defibrillator therapy

Abstract: A history of NSVT or MVT is a significant predictor for appropriate and successful ATP therapy. One in three patients with NSVT or MVT received appropriate ATP versus one in 10 patients without a history of NSVT or MVT over a 2-year period of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The occurrence of episodes of NSVT in subjects with left ventricular dysfunction is associated with an increase risk in arrhythmic events. This is true both for NSVTs observed during continuous ambulatory ECG monitoring [ 10 ] and for their documentation during ICDs interrogation [ 3 ]. Although there are few updated data on myocardial tissue characterization, it has classically been assumed that, in subjects with ischemic heart disease, the electrophysiological substrate of subjects with only episodes of NSVT, sustained MVT or VF is different.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of episodes of NSVT in subjects with left ventricular dysfunction is associated with an increase risk in arrhythmic events. This is true both for NSVTs observed during continuous ambulatory ECG monitoring [ 10 ] and for their documentation during ICDs interrogation [ 3 ]. Although there are few updated data on myocardial tissue characterization, it has classically been assumed that, in subjects with ischemic heart disease, the electrophysiological substrate of subjects with only episodes of NSVT, sustained MVT or VF is different.…”
Section: Discussionmentioning
confidence: 99%
“…However, the inability of S-ICD to deliver ATP therapy is another non-negligible concern. Indeed, the history of monomorphic VT or non-sustained ventricular tachycardia (NSVT) increases the chance of appropriate ATP therapy in 1 out of 10 patients and 1 out of 3 patients, respectively [ 62 ]. This condition may be considered among all discriminant factors in the choice between S-ICD and TV-ICD.…”
Section: Indications For S-icd Implantmentioning
confidence: 99%
“…Quast et al identified a prior history of monomorphic ventricular tachycardia or non-sustained ventricular tachycardia as the only predictor for appropriate and successful ATP. 13 In the pooled analysis of IDE study and EFFORTLESS registry, four patients of 882 patients required S-ICD extraction for a new pacing requirement after 651 days-only one was for ATP. 14 ing has also been shown to reduce inappropriate exclusions in cases of Brugada syndrome, congenital heart disease, 19 and hypertrophic cardiomyopathy.…”
Section: Patient Selectionmentioning
confidence: 99%